Feasibility Study of Office Procedure in Administrative Department for Barangay San Agustin in Quezon City: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Barangays are the primary planning and implementation units for government policies, plans, programs, projects, and activities in the community. Despite being a small local government unit, Barangay San Agustin has excellent administrative capabilities in managing its files and records. However, they sometimes face difficulty organizing their files due to a lack of storage and careless staff. Hence, Barangay San Agustin requires assistance to manage its office procedural system effectively. An observational and interview-based qualitative research approach was used in the administrative division of Barangay San Agustin in Quezon City to address this issue. A poll was conducted, and most personnel agreed to the proposed solution of Web Barangay, which allows residents to access information about public announcements, events, or public warnings. This technique will benefit people by making them more socially conscious of their surroundings. The researchers suggested that the Web Barangay have a mobile-friendly online application that requires little internet data to download. This study aimed to determine and show the Office Procedure of an Office Procedure Development Study at Barangay San Agustin in Quezon City.
Keywords: Feasibility study; Procedure; Barangay; Office; Admin Department; Staff; Constituents; Service; Issuance; Records